Própolis vermelha oriunda de Dalbergia ecastophyllum L. Taub. (Paraíba, Brasil): avaliação da toxicidade in vitro e in vivo e da atividade sobre bactérias de importância odontológica - Pontes, Marcela Lins Cavalcanti de (2018)
The pharmacological and toxicological effects of the Ethanol extract of Brazilian Red Propolis (EPVP) from João Pessoa (Paraíba, Brazil) were studied. Thin layer chromatography was used to characterize its major compounds. In order to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of the EPVP alone and in combination with Chlorhexidine (Clx), different in vitro antimicrobial studies were used. In carrying out the toxicological studies of the EPVP, tests of antioxidant activity and cytotoxicity were carried out using human red blood cells obtained from the Lauro Wanderley University Hospital blood bank. In the in vivo toxicity studies, the Brine Shrimp Test was performed using larvae of Artemia salina L., a microcatchus of the class Anostracea in the form of methanuplium, in addition to the chorioallantoic membrane toxicity test using fertilized chicken eggs, observing signs of vascular alteration . In the mouse assays, the Swiss species from the Thomas George / UFPB Bioternium were used and the genotoxicity and acute toxicity of the EPVP were evaluated. The antimicrobial activity experiments showed that EPVP promoted an antibacterial effect against species of the genus Streptococcus and Pseudomonas aeruginosa, with MIC ranging from 62.5 to 125 μg/mL and CBM ranging from 250 to 500 μg/mL. In the Clx association test, the substances MIC decreased by up to 16 fold, exhibiting synergism against S. mutans, S. oralis and S. salivarius. EPVP has been shown to have a potent antibiofilm effect against S. mutans, S. mitis, S. oralis and multispecies. EPVP at concentrations up to 500 μg/mL did not induce death in A. salina nor did it prove to be an irritant in the chorioallantoic membrane test in chicken eggs as it failed to promote vasoconstriction, hemorrhage or coagulation in the vascularization. In addition, EPVP induced weak hemolysis (<45%) at 500 μg / mL in all type A, B and O erythrocytes, inhibited phenylhydrazine-induced oxidation, and did not promote hemoglobin oxidation. Also, no micronuclei were detected in erythrocytes of rodents that used PLEV. In the evaluation of acute toxicity, after the oral administration of the EPVP, it was observed that the compound under study did not induce behavioral alterations nor did it alter the feed consumption of treated animals, without changing body weight, organ weight and biochemical parameters evaluated. In conclusion, these results suggest that EPVP is made antibacterial, with low cytotoxic, toxicological and genotoxic potency.